Spinal neurosurgery - Harrop, James S.; Maulucci, Christopher M. ([New York] : Oxford University Press, 2018)
This edited volume provides case-based, high yield content for the spine surgeon and neurosurgeons preparing for the American Board of Neurological Surgeons oral examination. It covers a wide array of spinal pathologies with their presentation, diagnosis, and treatment plans. Postoperative and complication management strategies are offered as well in order to prepare surgeons who can then provide comprehensive patient care for complex spine conditions.
Previously issued in print: 2018.
Includes bibliographical references.
Specialized.
Description based on online resource; title from home page (viewed on November 22, 2018).
Keywords: Spine -- Surgery; Nervous system -- Surgery